Analisis Faktor Yang Mempengaruhi Kepuasan Kerja Guru di SMPN 3 Depok - Iis Lestari; Halimatusha’diah Halimatusha’diah; Ismail Akbar Brahma; Siwi Puji Astuti (SAP (Susunan Artikel Pendidikan), 2026)
Teachers are the main pillar in improving the quality of education because they work directly in schools with students, principals, and other elements of society that determine the quality of students, schools, and the teachers themselves. Based on problems found in the field, not all teachers experience job satisfaction due to excessive administrative workloads. The research problem in this study is to analyze what factors influence teacher job satisfaction. Therefore, the purpose of this study is to analyze the factors that affect teacher job satisfaction at SMPN 3 Depok. The research method used in this study is descriptive qualitative. In the data collection process, the researcher used interviews, observations, and documentation. Interviews were conducted with five teachers at SMPN 3 Depok. The researcher also carried out observations accompanied by note-taking as part of documentation and observation studies regarding the factors that influence the performance of teachers at SMPN 3 Depok. The object of this study is teacher job satisfaction, while the subjects are teachers at SMPN 3 Depok. The results of this study show that the factors influencing teacher job satisfaction are: 1) salary, 2) promotion, 3) co-workers, and 4) work environment.